2021
DOI: 10.1016/j.bbagen.2021.129894
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic review of Parkin activation

Abstract: Parkin and phosphatase and tensin homolog (PTEN)-induced kinase 1 (PINK1) constitute a feed-forward signalling pathway that mediates autophagic removal of damaged mitochondria (mitophagy). With over 130 mutations identified to date in over 1000 patients with early onset parkinsonism, Parkin is considered a hot spot of signalling pathways involved in PD aetiology. Parkin is an E3 ligase and how its activity is regulated has been extensively studied: inter-domain interactions exert a tight inhibition on Parkin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Our previous report indicated that substrates of parkin are involved in many important cellular physiologic processes, including apoptosis, mitochondrial metabolism, and protein clearance [66]. In this study, we found that the protein expression of ARTS, one of the substrates of parkin, is down-regulated by PMN.…”
Section: Discussionsupporting
confidence: 49%
“…Our previous report indicated that substrates of parkin are involved in many important cellular physiologic processes, including apoptosis, mitochondrial metabolism, and protein clearance [66]. In this study, we found that the protein expression of ARTS, one of the substrates of parkin, is down-regulated by PMN.…”
Section: Discussionsupporting
confidence: 49%
“…A recurring model of parkin activity has posited that parkin forms dimers or oligomers to allow the catalytic RING2 domain of one molecule to contact the E2~Ub bound to another molecule (Gundogdu et al , 2021 ). We previously showed an absence of complementation in autoubiquitination assays (Sauve et al , 2018 ), but this left open the possibility of trans ‐active parkin dimers on the surface of mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PINK1 plays a role as ubiquitin kinase. A recent review goes into depth on the structural findings regulating Parkin activity [ 81 ]. PINK1 acts as a mitochondrial damage sensor, and when its import is arrested (under bioenergetics stress, loss in ∆Ψ m ), it accumulates on the OMM of dysfunctional mitochondria and phosphorylates Ub molecules (pUb).…”
Section: Regulation Of Mitophagymentioning
confidence: 99%